If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + -8) + -2 = -33 + -15v Reorder the terms: 5(-8 + 3x) + -2 = -33 + -15v (-8 * 5 + 3x * 5) + -2 = -33 + -15v (-40 + 15x) + -2 = -33 + -15v Reorder the terms: -40 + -2 + 15x = -33 + -15v Combine like terms: -40 + -2 = -42 -42 + 15x = -33 + -15v Solving -42 + 15x = -33 + -15v Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + 15x = -33 + 42 + -15v Combine like terms: -42 + 42 = 0 0 + 15x = -33 + 42 + -15v 15x = -33 + 42 + -15v Combine like terms: -33 + 42 = 9 15x = 9 + -15v Divide each side by '15'. x = 0.6 + -1v Simplifying x = 0.6 + -1v
| 18x^3-4x^2+10x= | | 55-55= | | 6.5x+x=74 | | -6(2+a)=48 | | 6r-60=12 | | 5a^2=-13a-6 | | 7x^2-3=67 | | 6+c=22 | | c^4-9c^2+20=0 | | 5x+2=6x+-4 | | 0=9x-y+5 | | 8x^2+5x+7=0 | | Y=4x^2+2x+1 | | v^2+7v+30=0 | | z-(-40)=33 | | x+20=1/3(234) | | Y=-0.2(40)+50 | | 4x-27+(x+39)=180 | | 4X^2+2x+1=y | | x-16=2/3x | | 7x-(3x+10)=-x+15 | | 5x^2+33x=-18 | | p=5-4p | | 7x-3-2x=24-4x | | 6-(-5-11)= | | N^2+10=6 | | 2(7x-9)=3(8x-1) | | 17x-(-4x-5)=70 | | 7b+4b+9-5= | | X^2-3x-1=x+3 | | -3y-10=-5 | | 2t-7=-4 |